Factors affecting the intention to choose a marine ecotourism destination in Ba Ria-Vung Tau province, Vietnam - Khanh, Pham Ngoc; Van, Nguyen Thi; Cuong, Ngo Anh (Journal of Tourism Management Research, 2024)
The objective of the article is to identify and evaluate the level of factors that influence the intention to choose a marine ecotourism destination and propose some management implications to help local government agencies and tourism businesses have appropriate policies and strategies to improve the quality of marine ecotourism and contribute to the development of the local tourism economy. Marine ecotourism is a form of nature-based tourism and sustainable marine tourism, associated with local cultural identity and community participation for sustainable development. Therefore, the author researched "factors affecting the intention to choose a marine ecotourism destination in Ba Ria-Vung Tau province, Vietnam." The study conducted data analysis based on 200 survey samples, processed with SPSS 23.0, software including assessing the reliability of the scales with Cronbach's Alpha test, exploratory factor analysis (EFA) with Barlett’s test and Kaiser-Meyer-Olkin (KMO); and regression analysis of factors affecting the intention to choose a marine ecotourism destination using F test and Sig significance level to test the hypotheses. The research results indicate that five factors, ranging from high to low in impact, influence the intention to choose a marine ecotourism destination: the source of destination information, travel motivation, ability to pay, the quality of information sources, and word-of-mouth on social networks.